Efek Tepung Ubi Jalar Ungu Terhdap Kadar LowDensity Lipoprotein (LDL) Tikus Putih Jantan Galur Wistar Model Obesitas - Vindi Atikatus Zuhro; Arisanty Nursetia Restuti; Adhiningsih Yulianti; Arinda Lironika (Puslitbang Sinergis Asa Professional, 2022)
Obesity is a nutritional problem caused by the accumulation of excess fat than needed. The purpose of this study was to determine the effect of purple sweet potato flour on HDL levels in obese male rats. This research is a True Experimental with pre-posttest control group. Samples were 24 male wistar rats weighing 200-300 grams. Samples were taken randomly in groups (K-), rats were fed with rat bio and water ad libitum. Group (K+), rats were induced with high fat diet ad libitum and given66% fructose drink ad libitum. (P) rats were induced by ad libitum high-fat diet and given ad libitum drinking of 66% fructose and 4.5 g of purple sweet potato flour intervention. Examination of HDL levels using the CHOD-PAP method. The results of One Way Anova Test Analysis (p>0.05)before treatment between groups there was no significant difference in LDL levels. And then after treatment there was no significant difference in LDL levels between groups. However, there was a decrease in LDL levels between treatement by 4 mg/dl. It can be concluded that purple sweet potato flour did not significantly reduce LDL levels in obese rats.